Karakterisasi Mikoriza di Kawasan Hutan Desa Fatusene Kecamatan Miomaffo Timur Kabupaten Timor Tengah Utara - Yolanda Getrudis Naisumu; Remigius Binsasi (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
The existence of allegations about the presence of various mycorrhizae in the forest area of Fatusene Village, East Miomaffo District, North Central Timor Regency, is a benchmark for assessing the characterization of mycorrhizae in the area. The purpose of this study was to isolate and identify mycorrhizae in the forest area of Fatusene Village, East Miomaffo District, North Central Timor Regency. Mycorrhizal identification begins with sampling the soil under the tree stands using the quadratic method. Soil samples were taken randomly at three points per observation plot with a depth of 0-30 cm from the base of the tree trunk. Separation of spores from soil samples was carried out using a wet sieve technique. Data analysis was carried out descriptively by identifying morphological characters including the shape and color of the spores. The results of mycorrhizal research found in the research location of the forest area of Fatusene Village are endomycorrhizal types, especially arbuscular vesicles. Characterization of mycorrhizal spores showed that there were three different spore genera in soil samples, namely the genus Glomus, Gigaspora and Acaulospora. The three genus found in the soil samples at the study location were present in each dominant tree with different numbers of individuals. The spores of the three mycorrhizal genus found at the study site were 65 spores, with the distribution of 35 spores genus Glomus, 20 spores genus Acaulospora and 10 spores the genus Gigaspora. The characters the genus glomus are round, slightly round, oval and brown and dark brown in, have hyphae and are equipped with oily fluid spots on cook spores. The characters the genus Acaulospora are round and oval in shape, blackish brown in color, brownish red and brownish yellow, have several layers of cell walls, one of which is dark in color. The characters the genus Gigaspora are irregular in shape, somewhat round and round, yellow, brownish yellow, to yellowish brown, large in size and black spore walls. Conclusion The mycorrhizae found in the study site were endomycorrhizal, especially arbuscular vesicles which consisted of 3 genera, namely Glomus, Acaulospora and Gigaspora. The characters of the genus glomus are round to oval in shape, dark brown in color, have hyphae and spotting of oil. The characters the genus Acaulospora are round and oblong, brownish yellow in color, have several layers of cell walls. The genus Gigaspora is slightly round and round, yellowish brown in color, large and black spore walls.